Pengaruh Penerapan Standar Akuntansi terhadap Kualitas Laporan Keuangan PT Telkom Indonesia 2020 - Zahra Nurfadillah; Dian Sabrina; Evaliana Evaliana; Amirah Firzanah; Kornelia Enik (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2026)
The objective of this study is to examine the impact of applying Financial Accounting Standards on the quality of PT Telkom Indonesia’s financial statements, specifically through the application of PSAK 72, which addresses revenue recognition, and PSAK 16, which addresses fixed assets. In addition, this research analyzes complementary aspects, such as human resources, accounting information systems, and internal control in the implementation process. This research employs a qualitative method using a literature review approach. The data used are secondary data collected from scientific journals, accounting standards, regulations, and the company’s financial statements. Data analysis was conducted through content analysis to determine the impact of the implementation of accounting standards on the quality of financial information. The findings show that the implementation of PSAK 72 and PSAK 16 improved the transparency, relevance, reliability, and comparability of financial statements. Revenue recognition became more accurate because it was based on the fulfillment of performance obligations to customers. However, several challenges were identified, including differences in contract interpretation, limitations in accounting systems, and the need to improve employee competence. The study concludes The application of financial accounting standards plays an important role in improving the quality of financial information. statements and strengthening corporate accountability. Effective implementation requires adequate accounting systems and competent human resources to support transparent and accurate financial reporting.